Pengaruh Jus Tomat dan Olahraga Intensitas Sedang Terhadap Penurunan Hipertensi Pada Lansia - Tiswan, Dinah Ayu Salsabila; Rusip, Gusbakti; Nasution, Sri Wahyuni (Syntax Literate, 2025)
Hypertension remains a major health issue among the elderly due to physiological changes affecting the cardiovascular system. This study aims to assess the effect of tomato juice consumption and moderate-intensity exercise on elderly individuals with hypertension. This study employed a quasi-experimental one-group pretest- posttest design. A total of 20 elderly participants from the Kodam Sunggal I/BB Village took part in a program involving daily consumption of 150 ml of tomato juice and elderly exercise sessions twice a week for ten days. Blood pressure was measured before and after the intervention using an aneroid sphygmomanometer. The results showed a significant decrease in systolic blood pressure (p = 0.002), while diastolic blood pressure also decreased but not significantly (p = 0.300). The conclusion of this study is that the combination of tomato juice consumption and moderate-intensity exercise is effective in reducing systolic blood pressure and can be considered a natural alternative in managing hypertension in the elderly.